Innovation Capacity and Entrepreneurial Intention: The Moderating Effects of Entrepreneurial Atmosphere - Ji, Yun; Bai, Yanhu (Journal of Applied Business and Economics, 2019)
There is natural relationship between innovative ability and entrepreneurial intentions (EI). Surprisingly, very little attention has been given to this important issue in previous literatures. Combining innovator’s DNA model with social cognitive theory, this paper collects 1263 samples to test the complex link between innovative capacity (operationalized as IC) and EI of potential entrepreneur. In addition, the effects of perceived entrepreneurial atmosphere (EA) on EI are examined. The results show that innovation capacity significantly affects EI, and perceived entrepreneurial desirability (ED) and feasibility (EF) mediates this relationship significantly. EA has direct effect on EI and indirectly changes the effect of IC through moderating the relationship between EF and EI. For robust test, we substitute dependent variable EI with entrepreneurial behavior and repeat the process above. The core results remain unchanged. The difference here is that actual entrepreneurial practice is not affected by attractiveness of start-up, innovator’s confidence to succeed in it is more important. This research confirms the necessary link between innovative capacity and EI, and substantially improves the explaining efficacy of classical EI models based on personality traits. Our findings indicate that policymakers need to pay more attention to training and improving potential entrepreneurs’ innovative ability and create social atmosphere more suitable for innovators entering the process of starting a new venture. Through increasing attractiveness and the simplicity to be an entrepreneur, government can motivate innovators to be more willing to start a business and also help them succeed at ease.